Analytical Computation of Sandy Slope Stability under the Groundwater Seepage and Earthquake Conditions - Yulin Lu; Xiaoran Chen; Li Wang (Advances in Civil Engineering)
Groundwater and earthquake are two of the factors behind the occurrence of slope instability. This paper focuses on the computation of the safety factor acting on a sandy slope when subjected to groundwater seepage and earthquake load. Based on the theory of limit equilibrium and a pseudodynamic method of analysis, a general solution for the dynamic factor of sandy slope containing two load conditions is proposed. In the solution, the effects of parameters such as water level, seismic acceleration coefficients, slope angle, and soil internal friction angle on the slope stability have been discussed. In order to evaluate the validity of the present formulation, the dynamic factors of safety computed by the present method are compared with those given by other cases. It is found that the results of the present method are in good agreement with those of the previous method. The results indicate that the dynamic of safety factor increases linearly with an increase in the soil internal friction angle but decreases with the slope angle and groundwater level and that the effects of direction and magnitude of the seismic inertia forces on the dynamic safety factor of sandy slope are different at different times.